Mechanochemical synthesis of nanocrystalline TiN/TiB2 composite powder - Shim, JH; Byun, JS; Cho, YW (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
TiN/TiB2, composite powder has been synthesized from a mixture of Ti and BN powders by high-energy ball milling. An abrupt displacement reaction between Ti and BN occurs in about 2 h. After the reaction, the crystallite sizes of TiN and TiB2 decrease continuously and become about 10 nm after 16 h of milling. (C) 2002 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.